The interpreter hears voices... Academic and Professional Perspectives X-rayed and interpreted - Ortega Herráez, Juan Miguel; Iliescu Gheorghiu, Catalina (MonTi Monografías de Traducción e Interpretación, 2016)
This paper aims to offer an X-ray of the evolution in Interpreting Studies, from the initial focus on Conference Interpreting to the current boom of Community Interpreting, without neglecting interpreter training, a constant theme in the discipline. Special attention will be paid to the tendencies detected in recent years (among which, a shift towards the history of the field) as well as to those “traditional” insights in Community Interpreting, such as discourse transfer processes, communicative situation specificities, contextual constraints (late 20th century) or the shift towards less agreed upon or elucidated issues (early 21st century), such as the necessary division between mediating and interpreting, quality, the interpreter’s role, codes of ethics and dilemmas, including the one on the employment of ad hoc interpreters. Through this paper we aim to contextualize the diverse contributions that make up this volume as an expression of current interests in this discipline.